2013
DOI: 10.1371/journal.pone.0063310
|View full text |Cite
|
Sign up to set email alerts
|

A DTI-Based Template-Free Cortical Connectome Study of Brain Maturation

Abstract: Improved understanding of how the human brain is “wired” on a macroscale may now be possible due to the emerging field of MRI connectomics. However, mapping the rapidly developing infant brain networks poses challenges. In this study, we applied an automated template-free “baby connectome” framework using diffusion MRI to non-invasively map the structural brain networks in subjects of different ages, including premature neonates, term-born neonates, six-month-old infants, and adults. We observed increasing bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 24 publications
(49 reference statements)
8
70
5
Order By: Relevance
“…This result is consistent with results from Tymofiyeva et al who found higher small-worldness in infants scanned shortly after normal term birth than in a group of preterm infants scanned at an average of ∼ 35 weeks after conception [52]. In their work, as here, rise in smallworldness was due to increased normalized CC values and stable normalized CPL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with results from Tymofiyeva et al who found higher small-worldness in infants scanned shortly after normal term birth than in a group of preterm infants scanned at an average of ∼ 35 weeks after conception [52]. In their work, as here, rise in smallworldness was due to increased normalized CC values and stable normalized CPL.…”
Section: Discussionsupporting
confidence: 93%
“…Some other recent works have focused on the examination of the structural connectome of young infants by performing tractography between numerous anatomical regions in the brain [3,41,50,52,53,58,54]. Takahashi et al examined results of full-brain tractography qualitatively and described trends across postmortem infants between 17 and 40 weeks [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of DWI studies have evaluated postnatal structural brain network development (Hagmann et al, 2012(Hagmann et al, , 2010Huang et al, 2013;Tymofiyeva et al, 2013;Yap et al, 2011) and demonstrated increasing integration and decreasing segregation (or clustering, Box 1) as hallmark features of childhood connectome maturation. Similarly, modules become increasingly interconnected and are further shaped, especially in the earliest postnatal years (Hagmann et al, 2010;Huang et al, 2013).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
“…Initial studies of neonatal structural networks have reported only dense local connectivity within segregated modules and few long-distance connections (12,15). In contrast, functional MRI reveals large-scale dynamic functional networks analogous to those seen in adults (16,17) and compatible with more advanced cerebral maturation.…”
mentioning
confidence: 97%